CHEMICAL PROCESSES APPLIED TO THE PRESERVATION OF ARTISANAL NATURAL JUICES - da Rocha Neto, João Bernardo; Taveira, José Henrique da Silva; Lima, Janderson do Carmo; Giongo, Pedro Rogério; Morgado, Cristiane Maria Ascari (Editora Impacto Científico, 2025)
Chemical preservation processes constitute important tools for microbiological control and for extending the shelf life of artisanal natural juices, especially in production contexts characterized by technological and operational limitations. These methods are based on the application of chemical agents with antimicrobial activity, acting through specific mechanisms such as medium acidification, disruption of cell membranes, inhibition of essential enzymatic systems, and induction of oxidative stress, resulting in microbial inactivation or growth inhibition. Among the main chemical processes employed in juice preservation are the use of organic acids, chemical preservatives authorized by sanitary legislation, sanitizing agents applied during the hygienization of raw materials, surfaces, and equipment, as well as, in specific situations, compounds such as sulfites and oxidizing agents. The effectiveness of these processes depends on multiple factors, including the concentration of the chemical agent, contact time, pH, food matrix composition, and the intrinsic resistance of the microorganisms present. From a technological standpoint, chemical processes present relevant operational advantages, such as ease of application, relatively low cost, and high efficiency against vegetative microorganisms, which explains their widespread adoption in both industrial and artisanal systems. However, their use may be associated with important limitations, including negative impacts on sensory attributes, regulatory restrictions regarding maximum usage limits, risks arising from improper application, and increasing consumer rejection of products with added chemical substances. Moreover, chemical processes applied in isolation rarely ensure adequate levels of microbiological safety, particularly against more resistant microorganisms. Thus, the judicious and technically grounded application of chemical processes, integrated with good manufacturing practices and combined preservation strategies based on the hurdle technology concept, constitutes an efficient approach to ensuring the microbiological safety, stability, and quality of artisanal natural juices.DOI: https://doi.org/10.56238/edimpacto2025.080-013